Megaprojects – An Anatomy of Perception: Local People's Perceptions of Megaprojects: The Case of Suramadu, Indonesia. Issue 2 (3rd April 2019) - Delphine,; Witte, Patrick; Spit, Tejo
Abstract: For decades, megaprojects have been on the agendas of policymakers worldwide. The positive effects are often illustrated at the national or regional level, whereas the negative impacts are mostly felt at the local level, which is something that most literature on megapro-jects neglects. Therefore, the following research focused on local people (residents and communities) to gain a deeper understanding of their perceptions of megaprojects, using the Suramadu Bridge in Indonesia as a case study. The research question was: "What are the perceptions of local people regarding the balance between the negative and the positive effects of megaprojects, and what factors affect their perceptions?" To answer this, both a survey and in-depth interviews were carried out. There were two main findings. Firstly, and interestingly, the vast majority of the respondents were supportive of the project, mainly for emotional reasons and because of their cultural background. However, certain groups reported experiencing the negative externalities of the project, which shows how contested megaprojects are in the eyes of local people. Secondly, an exploratory factor analysis revealed that there are three factors underlying people's perceptions, namely immaterial benefits, material benefits and specific employment opportunities. The strongest factor turned out to be, again surprisingly, immaterial benefits, implying that people may perceive a different reality caused by the project, involving intangible aspects such as pride and a new identity. We suggest that including people's perceptions in megaproject studies can contribute to more inclusive megaproject development processes.